Nongovernmental development organizations and the poverty reduction agenda : the moral crusaders - Makuwira, Jonathan J. (Routledge; New York, 2014)
"The Non-Governmental Development Organisations (NGDOs) have, over the past two decades, entered centre stage in their active participation in the social, political and economic issues affecting both the developing and developed world. This book offers a highly stimulating and concise summary of the NGDO sector by examining their history and metamorphosis; their influence on the social, political and economic landscapes of the 'Northern' and 'Southern' governments and societies. The author analyses competing theoretical and conceptual debates not only regarding their contribution to the global social political dynamism but also on the sector's changing external influence as they try and mitigate poverty in marginalized communities. This book presents NGDOs as multidimensional actors propelled by the desire to make a lasting change but constrained by market-oriented approaches to development and other factors both internal and external to their environment. While a lot of attention has been given to understanding international NGDOs like World Vision International, Oxfam, Care International and Plan International, this book offers a critical analysis of grassroots organizations-- those NGDOs founded and established by locals and operate at the deepest end of the development contexts.This work will be of interest to students and scholars in a range of areas including Development Studies, International Organizations and Globalization. "--
"This book offers a highly stimulating and concise summary of the NGDO sector by examining their history and metamorphosis; their influence on the social, political and economic landscapes of the 'Northern' and 'Southern' governments and societies"--
Includes bibliographical references (pages 166-167) and index.
Keywords: Non-governmental organizations; Poverty; Economic development; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Treaties